THE INFLUENCE OF E-SERVICE QUALITY AND CUSTOMER EXPERIENCE ON PURCHASING DECISIONS OF DIPONEGORO UNIVERSITY FISIP STUDENTS AS USERS OF LAZADA E-COMMERCE - Shania Agitta Tarigan; Sudharto P Hadi; Apriatni E Prihatini (Jurnal Ilmu Administrasi Bisnis, 2025)
Abstract: At the era of digital, internet use has become an important part of everyday life, including shopping online through e-commerce. Lazada, as the leading e-commerce platform in Indonesia, is facing challenges with declining Top Brand Index (TBI), sales volume and web visits, as well as customer complaints regarding the quality of service and experience at Lazada. This research aims to determine the influence of e-service quality and customer experience on purchasing decisions at Lazada e-commerce. This type of research is explanatory research with samples taken using non-probability sampling techniques and a purposive sampling approach. Data was collected through questionnaires from 100 respondents, FISIP students at Diponegoro University, Lazada users. Data analysis used validity test, reliability test, correlation coefficient test, coefficient of determination test, simple linear regression analysis, multiple linear regression analysis, t test, and F test with IBM SPSS Statistics version 29. The results showed a positive and significant influence between e- service quality and customer experience on purchasing decisions, both partially and simultaneously. Based on these results, it is recommended that the company improve the quality of Lazada's services, especially the system so that it is not susceptible to problems, as well as simplifying the appearance of Lazada's e-commerce to make it more user-friendly. Keywords: e-service quality, customer experience, purchasing decision. Abstraksi: Dalam era digital, penggunaan internet menjadi bagian penting kehidupan sehari-hari, termasuk berbelanja online melalui e-commerce. Lazada, sebagai platform e-commerce terkemuka di Indonesia, menghadapi tantangan dengan menurunnya Top Brand Index (TBI), volume penjualan, dan kunjungan web, serta keluhan pelanggan terkait kualitas layanan dan pengalaman di Lazada. Penelitian ini bertujuan mengetahui pengaruh e-service quality dan customer experience terhadap keputusan pembelian di e-commerce Lazada. Tipe penelitian ini adalah explanatory research dengan sampel diambil menggunakan teknik non-probability sampling dan pendekatan purposive sampling. Data dikumpulkan melalui kuesioner kepada 100 responden, mahasiswa FISIP Universitas Diponegoro pengguna Lazada. Analisis data menggunakan uji validitas, uji reliabilitas, uji koefisien korelasi, uji koefisien determinasi, analisis regresi linear sederhana, analisis regresi linear berganda, uji t, dan uji F dengan IBM SPSS Statistics versi 29. Hasil penelitian menunjukkan pengaruh positif dan signifikan antara e-service quality dan customer experience terhadap keputusan pembelian, baik secara parsial maupun simultan. Berdasarkan hasil ini, disarankan perusahaan memperbaiki kualitas layanan Lazada, khususnya sistem agar tidak rentan mengalami kendala, serta menyederhanakan tampilan e-commerce Lazada agar lebih user-friendly. Kata Kunci: e-service quality, customer experience, keputusan pembelian